2020
DOI: 10.1111/joor.12928
|View full text |Cite
|
Sign up to set email alerts
|

Exercise‐based swallowing intervention (McNeill Dysphagia Therapy) with adjunctive NMES to treat dysphagia post‐stroke: A double‐blind placebo‐controlled trial

Abstract: Background Dysphagia following stroke is prevalent; however, dysphagia treatment is often applied haphazardly and outcomes unclear. Neuromuscular electrical stimulation (NMES) has received increased attention as a treatment for post‐stroke dysphagia; but application data remain conflicted. Objective This study investigated effectiveness and safety of an exercise‐based swallowing therapy (McNeill Dysphagia Therapy: MDTP) +NMES for dysphagia rehabilitation following stroke. Methods Stroke patients (n = 53, x̅ ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
66
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(75 citation statements)
references
References 28 publications
(41 reference statements)
2
66
0
3
Order By: Relevance
“…A total of 21 articles were found, of which eleven were focused on experimental researchs [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ] and nine were randomized-controlled trials [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. The methodological characteristics of the analysed studies are shown in Table 2 and, in Table 3 , the characteristics of the interventions applied in them are presented.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 21 articles were found, of which eleven were focused on experimental researchs [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ] and nine were randomized-controlled trials [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. The methodological characteristics of the analysed studies are shown in Table 2 and, in Table 3 , the characteristics of the interventions applied in them are presented.…”
Section: Resultsmentioning
confidence: 99%
“…The application of NMES was not conducted using the same parameters in the analysed investigations. Regarding the application frequency, the choice of 80 Hz was the most widely used [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 35 , 36 , 37 , 39 , 40 , 41 , 42 , 45 ], although, in several cases, this parameter was not mentioned [ 34 , 38 , 44 , 46 ] and in another two studies the authors selected lower frequencies (60 [ 47 ] and 30 Hz [ 43 ]). In all cases, the results were statistically significant; even those studies which used lower frequencies obtained significant reductions in oral and pharyngeal transit time [ 47 ], significant decreases in the severity of penetration and aspiration [ 43 ] and significant increases in the level of oral intake and quality of life [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with mild dysphagia may present with coughing when drinking water, which affects patients' confidence in eating, and repetitive fever 10 . Severe patients are prone to aspiration pneumonia and asphyxia, malnutrition, etc, and it seriously impairs the quality of life of patients, and sometimes even endanger the lives of patients 11 . Therefore, early assessment of swallowing function after stroke, active and effective rehabilitation treatment based on the specific conditions of patients, has significant effects on shortening the course of disease, reducing the mortality and the burden of patients and society, and improving the quality of life 12 …”
Section: Introductionmentioning
confidence: 99%